Strength Back – A qualitative study on the co-creation of a positive psychology digital health intervention for spinal surgery patients - Van Der Horst, Annemieke Y.; Bohlmeijer, Ernst T.; Schreurs, Karlein M. G.; Kelders, Saskia M. (Frontiers in Psychology, 2023)
Introduction Spinal surgery patients often experience pain as well as stress, anxiety or even depression before surgery, highlighting the need for better mental preparation before undergoing surgery. Acceptance and Commitment Therapy and positive psychology have proven effective in coping with chronic pain and providing long-term skills that enhance psychological flexibility and mental well-being. The aim of this study is to develop a digital intervention (app) based on Acceptance and Commitment Therapy and positive psychology in co-creation with all stakeholders, including patients and professionals. The aim of the intervention is to increase psychological flexibility and positive skills of spinal surgery patients to promote long-term resilience. Material and methods In this qualitative study, individual, semi-structured interviews were held with healthcare professionals (N=9) and spinal surgery patients (N=12) to identify contextual factors and needs for the app. Subsequently, three focus-group sessions were held with healthcare professionals and newly recruited patients to specify relevant values. Also, a first version of the app, named Strength Back, was developed using a participatory design. Results The interviews confirmed the need for information and digital support to cope with insecurity, anxiety and pain, both before and after surgery. Based on iterative steps in the focus-group sessions, thirteen modules were developed focusing on procedural information, pain education, psychological flexibility and mental well-being. Discussion The intervention Strength Back, containing information as well as Acceptance and Commitment Therapy and positive psychology exercises, has the potential to increase psychological flexibility, enhance well-being and improve postoperative recovery after spinal surgery.